Prediksi Kualitas Biodiesel Berdasarkan Komposisi Asam Lemak Bahan Mentah (Minyak-lemak) - Joelianingsih .; Armansyah H. Tambunan; Tatang H. Soerawidjaya; Yasuyuki Sagara; Kamaruddin Abdullah (Jurnal Keteknikan Pertanian, 2008)
Abstract The characteristics of biodiesel are similar to diesel fuels, and therefore biodiesel becomes a strong candidate to replace the diesel fuels if the need areses. Biodiesel standard- so called SNI 04-7182-2006 has been approved by the Indonesian National Standardization Agency (BSN). The basic fuel properties for biodiesel are influenced by the fatty acid composition of the feedstock such as the sensity, viscosity, cetane number, heating value and cloud point. Therefore, the value of these properties can be predicted from the fatty acids composition of the feedstock using the blending equations. This work uses pure component data for methyl palmitate, methyl stearate, methyl oleate, and methyl oleate to develop and test blending equations for the prediction of the basic fuel properties. The results from the blending equations are compared with literature values for biodiesel for a number of triglyceride sources such as palm and jatropha oils. Typical average errors are less than 10% for the density, cetane number and healting value. The blending equation for the viscosity and cloud point are suitable only for a speciefed biodiesel. Keywords: biodiesel, basic fuel properties, blending equation , SNI Diterima: 28 Mei 2007; Disetujui: 22 Agustus 20017